What clinical signs best identify severe illness in young infants aged 0-59 days in developing countries? A systematic review. - Opiyo, N; English, M (2011)
Despite recent overall improvement in the survival of under-five children worldwide, mortality among young infants remains high, and accounts for an increasing proportion of child deaths in resource-poor settings. In such settings, clinical decisions for appropriate management of severely ill infants have to be made on the basis of presenting clinical signs, and with limited or no laboratory facilities. This review summarises the evidence from observational studies of clinical signs of severe illnesses in young infants aged 0-59 days, with a particular focus on defining a minimum set of best predictors of the need for hospital-level care. Available moderate to high quality evidence suggests that, among sick infants aged 0-59 days brought to a health facility, the following clinical signs-alone or in combination-are likely to be the most valuable in identifying infants at risk of severe illness warranting hospital-level care: history of feeding difficulty, history of convulsions, temperature (axillary) ≥37.5°C or <35.5°C, change in level of activity, fast breathing/respiratory rate ≥60 breaths per minute, severe chest indrawing, grunting and cyanosis.